2014
DOI: 10.1038/cddis.2014.269
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 and CXCR7 transduce through mTOR in human renal cancer cells

Abstract: Treatment of metastatic renal cell carcinoma (mRCC) has improved significantly with the advent of agents targeting the mTOR pathway, such as temsirolimus and everolimus. However, their efficacy is thought to be limited by feedback loops and crosstalk with other pathways leading to the development of drug resistance. As CXCR4–CXCL12–CXCR7 axis has been described to have a crucial role in renal cancer; the crosstalk between the mTOR pathway and the CXCR4–CXCL12–CXCR7 chemokine receptor axis has been investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 53 publications
3
64
0
Order By: Relevance
“…Tsaur et al [140] observed increased chemotactic activity of prostate cancer cells resistant to everolimus, a process that was characterized by significant alterations of integrin α2, α5 and α1 expression profiles as well as the reactivation of Akt, whereas treatment of sensitive prostate cancer cells with everolimus resulted in decreased tumour cell chemotaxis, migration and invasion. Similarly, Ierano et al [141] demonstrated that the effect of CXCR (CXC chemokine receptor) 4, CXCR7 and mTOR inhibitors was additive in impairing migration and cell growth. Additionally, they observed that everolimus inhibited CXCL12 (CXC chemokine ligand 12)-induced migration, wound healing and cell growth.…”
Section: Cellular Effects Of Everolimusmentioning
confidence: 96%
See 1 more Smart Citation
“…Tsaur et al [140] observed increased chemotactic activity of prostate cancer cells resistant to everolimus, a process that was characterized by significant alterations of integrin α2, α5 and α1 expression profiles as well as the reactivation of Akt, whereas treatment of sensitive prostate cancer cells with everolimus resulted in decreased tumour cell chemotaxis, migration and invasion. Similarly, Ierano et al [141] demonstrated that the effect of CXCR (CXC chemokine receptor) 4, CXCR7 and mTOR inhibitors was additive in impairing migration and cell growth. Additionally, they observed that everolimus inhibited CXCL12 (CXC chemokine ligand 12)-induced migration, wound healing and cell growth.…”
Section: Cellular Effects Of Everolimusmentioning
confidence: 96%
“…This echoes a previous study by Bresccia et al [179] who reported that dual inhibition with PI3K and MAPK inhibitors was superior in efficacy to inhibition of a single pathway alone. Recently, Ierano et al [141] described a novel method to resensitize RCC to everolimus treatment via inhibition of the CXCR4-CXCL12-CXCR7 axis. The cross-talk between CXCR4-CXCL12 and PI3K/mTOR has been well established in various cancer cells [26,27,29].…”
Section: Molecular Effects Of Everolimusmentioning
confidence: 99%
“…mTORC1 comprises regulatory-associated protein of mTOR (RAPTOR), proline-rich Akt substrate 40 kDa (PRAS40), mammalian lethal with Sec13 protein 8 (mLST8), and DEP domaincontaining mTOR-interacting protein (DEPTOR), which has an inhibitory function on mTORC1. The classical mTORC1 positive inputs are growth factors, chemokines [4], nutrients (glucose, amino acids), and cell energy status (i.e., high ATP:AMP ratio) [1]. Growth factors and cytokines stimulate mTORC1 mainly through the phosphoinositide 3-kinase (PI3K)/Akt signaling pathway ( Figure 1).…”
mentioning
confidence: 99%
“…Recent studies have shown CXCR4 signaling through mTOR in pancreatic cancer, gastric cancer, and T-cell leukemia cells (10)(11)(12)(13). In human renal cancer cells, CXCL12 induces phosphorylation of the specific mTOR targets, P70S6K and 4EBP1 (14), and CXCR4 and mTOR inhibitors have been reported to impair human renal cancer migration ( Fig. 1; ref.…”
Section: Introductionmentioning
confidence: 99%